ATM knock out alters calcium signalling and augments contraction in skeletal muscle cells differentiated from human urine-derived stem cells - Giulia Dematteis; Giulia Lecchi; Giulia Boni; Diana Pendin; Carla Distasi; Mariagrazia Grilli; Dmitry Lim; Luigia Grazia Fresu; Maria Talmon (Cell Death Discovery)
Abstract Ataxia-telangiectasia (A-T) is a rare neurodegenerative disorder caused by the deficiency of the serine/threonine kinase ataxia telangiectasia mutated (ATM) protein, whose loss of function leads to altered cell cycle, apoptosis, oxidative stress balance and DNA repair after damage. The clinical manifestations are multisystemic, among them cerebellar degeneration and muscular ataxia. The molecular mechanism by which ATM loss leads to A-T is still uncertain and, currently only symptomatic treatments are available. In this study, we generated a functional skeletal muscle cell model that recapitulates A-T and highlights the role of ATM in calcium signalling and muscle contraction. To this aim, by using CRISPR/Cas9 technology, we knocked out the ATM protein in urine-derived stem cells (USCs) from healthy donors. The resulting USCs-ATM-KO maintained stemness but showed G2/S cell cycle progression and an inability to repair DNA after UV damage. Moreover, they showed increased cytosolic calcium release after ATP stimulation to the detriment of the mitochondria. The alterations of calcium homoeostasis were maintained after differentiation of USCs-ATM-KO into skeletal muscle cells (USC-SkMCs) and correlated with impaired cell contraction. Indeed, USC-SkMCs-ATM-KO contraction kinetics were dramatically accelerated compared to control cells. These results highlight the relevant function of ATM in skeletal muscle, which is not only dependent on a non-functional neuronal communication, paving the way for future studies on a muscular interpretation of A-T ataxia.